Improving the strategy to create a profitable and sustainable business in the era of economic competition in Indonesia - Dyanasari, Dyanasari; Siswadi, Bambang; Hindarti, Sri; Askafi, Eka; Mulyaningtiyas, Ratna Dewi (Linguistics and Culture Review, 2021)
This project aims to improve business strategies to increase profits and sustainability in the era of business competition. The data that we use to answer the discussion of this study is sourced from some literature published in several journals such as books, procedures at other times. We then analyzed the data using a phenomenological approach, a method for exploring the data and then analyzing it under an in-depth interpretation approach to the coding system and evaluating analysis to provide the data as findings to answer high-quality questions. The data search is carried out by procedures and electronically with a keyword system. Based on the existing data and the discussion, we can finally conclude that the results include strategies to increase profits and business continuity in this competitive era is the ability instead of moving a business to understand the business world, study business strategies, understand and know the business competition system and have extensive knowledge of business that is run in an era full of intense competition. Hopefully, these insights to be a good input material to support future studies.